Polymeric Resins with Sulfonic or Quaternary Ammonium Groups Used as High-Capacity Adsorbents of Tetracycline - Boulett-Neira, A; Boulett-Neira, A (ELSEVIER, 2025)
In this research, polymeric resins based on poly(3-sulfopropyl acrylate potassium salt) (P(SPAK)) and poly([3-(methacryloylamino)propyl] trimethylammonium chloride) (P(MAPTAC)) were prepared and tested as tetracycline (TC) adsorbents. These resins were characterized by chemical, thermal, morphological, surface techniques and by evaluating their hydration properties. P(SPAK) presented higher swelling ratio (27.6 g g-1) than P (MAPTAC) (15.6 g g-1). Also, we optimized by a multi-variate method the amount of resin and pH in TC removal using an experimental design, and then univariate evaluation of ionic strength concentration, contact time, TC concentration and temperature, reaching values of 713 mg g-1 for P(SPAK) at pH = 3 and 1067 mg g-1 for P (MAPTAC) at pH = 10.5, influenced by the chemical speciation of the pollutant and the resin. The low ionic strength favored adsorption, while high concentrations of KCl reduced it. The kinetics followed the Elovich model, reaching equilibrium in 1440 min. Freundlich isotherms indicated multilayer adsorption and energy heterogeneity. The process was endothermic and spontaneous with higher efficiency at higher temperatures. Finally, the resins proved to be reusable up to three consecutive adsorption-desorption cycles.